(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Nurses form the backbone of healthcare systems, yet in Pakistan, the profession continues to face significant challenges related to job dissatisfaction and migration intentions. Persistent faces many issues;likewise, inadequate pay, excessive workloads, poor working environments, and limited career advancement opportunities have contributed to high turnover rates and outward migration. Conversely, attractive overseas opportunities, including higher salaries, safer workplace conditions, and professional development, exert a strong pull on the nursing workforce. Understanding the balance of these push and pull factors is crucial to addressing workforce shortages and improving retention in tertiary care hospitals. Objective: This study aimed to examine the impact of push and pull factors on job satisfaction and migration decisions among nurses working at Nishtar Hospital, Multan. Methods: A descriptive cross-sectional survey was conducted among 300 registered nurses at Nishtar Hospital. Participants with at least one year of clinical experience were recruited using proportionate stratified random sampling. Data were collected through a structured, validated questionnaire consisting of three sections: demographics, push and pull factors, and job satisfaction/migration intentions. Responses were recorded on a 5-point Likert scale. Data were analyzed using SPSS version 26, with descriptive statistics used to summarize variables and Chi-square tests applied to determine associations. A p-value ≤ 0.05 was considered statistically significant. Results: The majority of respondents were female (80%), aged 26–35 years (75%), and most held a bachelor’s degree (67%). Regarding push factors, low wages (62%), excessive workload (68%), and high patient-to-nurse ratios (65%) were the most frequently cited sources of dissatisfaction. Among pull factors, higher salaries (72%), better working conditions abroad (68%), and professional development opportunities (63%) emerged as the most influential drivers of migration. Overall, 50% of nurses reported dissatisfaction, while only 28% expressed satisfaction with their current roles. Statistical analysis confirmed significant associations between both push and pull factors with migration intentions and job satisfaction (p < 0.05). Conclusion: The findings highlight that economic stressors, heavy workloads, and unsafe working conditions are key push factors undermining nurse satisfaction, while financial incentives and career growth opportunities abroad act as powerful pull factors encouraging migration.Urgent interventions are required to improve salaries, reduce workload, and enhance professional development opportunities in Pakistan’s healthcare system. By addressing these challenges, tertiary hospitals can strengthen retention, improve job satisfaction, and mitigate the growing trend of nurse migration.